Like feathers - Gullion, Lauren, author; Schwartz, Steven, advisor; Doenges, Judy, committee member; Malpezzi Price, Paola, committee member (Colorado State University. Libraries, 2012)
These pages represent the beginning of a novel-in-progress centering on a half-white half-Mexican woman named Noemi. In the Prologue, we meet Noemi and her childhood friend Phillip when both are in their early 30s. Part One goes back to follow a first-person narration with Noemi at age 12 to age 17 in the late 1980s to early 1990s. Set primarily in the Los Angeles suburb of Calabasas, Noemi moves through interactions with Phillip as well as other coming-of age and self-exploration moments leading up to the afternoon the 1992 Los Angeles Riots broke out. Part Two then follows Noemi’s best friend Brandi in a third-person narration through the same time period, focusing primarily on Brandi’s romantic relationship with Lorenzo, a Mexican man twice her age. The latter part of the book not included here will cover what happens during the Riots--highlighted by an altercation that leaves Lorenzo critically injured--and then leading up to the present day visited in the Prologue. A story about identity, exposed here are the ways in which individuals so often strive to break into a new or at least redefined identity, only to be stunted in their efforts due to the ways in which we are so often defined more by place and circumstance than own inner beings and longings. Also at play are the illusion of perfection and the often times detrimental effect of striving for such an illusion.